Anastomosis of the medial digital artery in a mare following traumatic laceration. (29th February 2016) - Isgren, C. M.; Milner, P. I.
Summary: A 7‐year‐old Warmblood mare presented with blood loss from a laceration of the medial digital artery sustained in the field. The mare was initially managed conservatively by pressure bandaging but the bleeding did not stop. After a blood transfusion the mare underwent arterial repair under general anaesthesia and was initially managed in a cast post operatively. Doppler ultrasonography 4 days post operatively confirmed effective blood flow distal to the arterial anastomosis and the mare was discharged from the hospital. At 6 months follow‐up the owner reported that the mare was sound at the trot with an excellent cosmetic outcome of the surgical site.